THE CORRELATION OF CONCENTRATION OF C REACTIVE PROTEIN AND PROCALCITONIN WITH WHITE BLOOD CELLS COUNT IN ACUTE INFECTION AND SEPSIS - Đorđević, Jelena M; Pavlovic, Sofija; Makulovic, Stefan; Todorovic, Petar; Osmanovic, Emina; Terzic, Kristina; Mihaljevic, Olgica (Medicinski podmladak, 2024)
Introduction: Infection is a local response to an active or passive pathogen penetration and/or its reproduction in the biological system. Unlike the infection, sepsis is characterized by a systemic inflammation response of the host. The most commonly used biomarkers for the diagnosis of infections and sepsis are C reactive protein (CRP) and procalcitonin (PCT).Aim: The aim of our study was to examine the correlation of CRP and PCT with white blood cells (WBC) count in the patients with acute infection and sepsis.Мaterial and Methods: This retrospective study included 69 patients who underwent a blood test at the Central Laboratory of University Clinical Center of Kragujevac to determine the presence of infection/sepsis during hospitalization. Patients were divided into two groups: patients with local infection of different localization and patients with sepsis. In the group of patients with local infection, four subgroups were distinguished: patients with respiratory tract infections, urinary tract infections, gastrointestinal and hepatobiliary infections, and skin infections. The control group comprised 40 healthy subjects. The study analyzed data about WBC count, neutrophil and lymphocytes count as well the concentration of CRP and PCT.Results: The analysis of mentioned parameters indicated that patients with infection/sepsis had significantly higher values ​​of WBC (p
Keywords: C reactive protein; infection; leukocytes; procalcitonin; sepsis